Answer:
g = -39/5
Step-by-step explanation:
g(-5) = -7(-5)+4
-5g = +35+4
-5g = 39
-g = 39/5
g = -39/5
Answer:
(0, -8)
Step-by-step explanation:
Answer:
1. 44 + 3x
2. 2y - 8
3. x - 6
15. 
16. 
17. 
Step-by-step explanation:
1. 7² + 2² - 5 - 4 + 3x
49 + 4 - 5 - 4 + 3x
53 - 5 - 4 + 3x
48 - 4 + 3x
44 + 3x
2. - y - 5 + y + 2(2y-y) - 3
-y - 5 + y + 4y - 2y -3
-y - 5 + 5y - 2y - 3
4y - 2y - 5 - 3
2y - 8
3. 5x -3 - x - 3(x + 1²)
5x - 3 - x - 3x - 3
4x - 3x - 3 -3
x - 3 -3
x - 6
15.
=
=
=
→ 
16. 
= 
= 
=
→
→ 
17. 
= 
= 
=
→ 
Hope this helps.
r = 2 inches
total h of the cylinder = 6+6+6 = 18 inches




